Innovation of Utilization of Materials Research and Development Results in the Framework of Fulfilling the Defense Equipment of the Indonesian Army (Case Study of Battlefield Management System) - Yudho Setiarsono; Hakimul Ikhwan; Umi Listyaningsih (Populasi, 2022)
This study aims to map policy innovations downstream of material R&D results, especially the Battlefield Management System (BMS) in fulfilling the independent and modern defense equipment of the Indonesian Army. This research was conducted using a qualitative method and a case study strategy. The determination of the research location is based on the existence of phenomena in research and development activities carried out within the Indonesian Army. This study used qualitative research methods to explain the research problem in-depth. Determination of informants/resource persons based on purposive sampling resulted in six people consisting of officials who formulate the R&D policies of the Indonesian Army, officials from elements of R&D activities implementing the Battlefield Management System, elements from domestic defense industry actors in the R&D activities of the Battlefield Management System, as well as elements from researchers/teachers and military observers from non-governmental organizations. Furthermore, the data analysis was carried out based on the theories and concepts of public policy and then the data interpretation process was carried out. The result of this study is the public policy innovations in realizing downstream policies. BMS is the result of innovation which is proven to meet the 13 determinants of innovation. Downstream policies play a role in realizing BMS products in the fulfillment of the defense equipment of the Indonesian Army. BMS is a modern defense equipment of the Indonesian Army, fulfilling aspects of complexity, technological progress and speed. Although not-yet fully realized due to the not-yet optimal of the triple helix policy, BMS products based on independence still face problems that there are still conflict of interests, research funding, production costs and indications of weak political will of the Indonesian Army to use domestic products. Recommendations from this research are the need for prioritization, continuous and consistent budgeting and procurement (mass production) and budgeting for superior material R&D results as a form of reward. In addition, there is a need for policies and regulations that can protect the products of material R&D against the competitiveness of similar products from abroad.